Analysis of Religious Issues and Interfaith Relations from Surah Al-Baqarah: 256, A Study of the Tafsir Al-Azhar - Yunitasari, Hanifatul Sahro; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Freedom of religion is a topic that is constantly discussed. In some cases, the reviewers of this issue base their views on the Qur'an. Verse 256 of the letter al-Baqarah is one of the most quoted and referenced verses, especially the root of the verse, which reads la ikraha fi al-din. Buya Hamka, in the interpretation of al-Azhar, uses a content analysis approach. Through this approach, the author tries to describe analytically and interpretively. This research method is categorized into a qualitative type that focuses on literature and library materials as data sources. The results of this study are as follows: First, Buya Hamka explained that the verse and the previous verse (Al-Baqarah verse 255) are closely related and inseparable. He explained that the Throne verse is the most important teaching in Islam, about knowing ḥ idan. Second, Buya Hamka in Tafsir al-Azhar explained the verse using the bi al-Ma'sūr method. Third, according to Buya Hamka, based on the Qur'an, letter al-Baqarah verse 256, Islam does not allow coercion in embracing religion.